VISUAL PHOTOGRAPHY HEGEMONY IN JUNK FOOD MEDIA PROMOTION - Dinata, Ramanda Dimas Surya; Paramaartha Nugraha, Putu Dony (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2020)
Abstract Basically, the visual elements of photography in the media promotion of junk food functioned as a representation that represents the identity of a brand. The effectiveness in providing information in seeing the real visual is more chosen as one of the messengers who are able to bring the human mind into the interpretation of truth as a factor in the emergence of a sense of trust. In the visual world, hegemony involves the packaging of art in such a way that it produces forms that distort and escape reality. The problem faced is when visual photography in promotional media is not really a representation of the actual product. Media promotion (advertising) on Junk Food as a product of modern culture that unconsciously has made the hegemony of society into a culture of consumerism. This research will focus on forms of aesthetic photographic hegemony construction and their implications. This research approaches postmodern, consumerism, and photography aesthetics. The data analysis will use qualitative data that is primary data both from interviews and observations and secondary data in the form of documents, articles, and examples of reference ads in various media. There are three representations of the aesthetic hegemony of photography in promotional media that are, 1) Whereas in the present embodiment of promotional media the exchange value is no longer prioritized to the use value or meaning contained in it but has shifted by prioritizing the image value. 2) The high culture of consumerism causes the community without realizing it has become hegemony through the art of photography which is manipulative connotation. 3) Signs on the object of consumption in fact tend to be used to mark social relations, determine the prestige, status and certain social symbols that cannot be rejected as markers of modern society.